Race, Rural Residence, and Control of Diabetes and Hypertension - Mainous, Arch G. (Copyright 2004 Annals of Family Medicine, Inc., 2004)
PURPOSE African Americans are at increased risk for diabetes mellitus and hypertension, and rural residents have historically had decreased access to care. It is unclear whether living in a rural area and being African American confers added risks for diagnosis and control of diabetes and hypertension. The purpose of this study was to examine the prevalence of diagnosed diabetes and hypertension, as well as control of both conditions, among rural and urban African Americans and whites. METHODS We conducted an analysis of the Third National Health and Nutrition Examination Survey (1988–1994). Non-Hispanic African Americans and non-Hispanic white adults 20 years and older were classified according to rural or urban residence (n = 11,755). Investigated outcomes were previously diagnosed diabetes mellitus and hypertension and control of diabetes and hypertension. RESULTS The prevalence of diagnosed diabetes was 4.5% for urban whites, 6.5% for rural whites, 6.0% for urban African Americans, and 9.5% for rural African Americans. Among patients with diagnosed diabetes, 33% of rural whites, 43% of urban whites, 45% of urban African American, and 61% of rural African Americans had glycosylated hemoglobin (HbA(1c)) levels of 8% or higher (P <.01). Among patients with diagnosed hypertension, 11% of rural whites, 13% of urban whites, 20% of urban African Americans, and 23% of rural African Americans had diastolic blood pressure greater than 90 mmHg (P <.01). In regression models controlling for relevant variables, including body mass index, health status, access to care, education, income, and insurance, compared with rural African Americans, rural and urban whites were significantly more likely to have better glycemic control and diastolic blood pressure control. Urban African Americans also had better diabetes control than rural African Americans. CONCLUSIONS In this nationally representative sample, rural African Americans are at increased risk for a lack of control of diabetes and hypertension.